An analytical study of easterly waves over southern peninsular India during the northeast monsoon 2010 - GEETHA, B.; BALACHANDRAN, S. (MAUSAM, 2014)
Easterly wave characteristics over southern peninsular India during the northeast monsoon season of 2010 are examined by means of synergetic analysis involving synoptic, statistical and numerical methods. NCEP 6-hourly reanalysis datasets of zonal and meridional winds, vertical velocity, temperature and net long wave radiation at 2.5° × 2.5° grid resolution for the period 20th October to 31st December, 2010 form the main database for the analysis. During this period, 3 easterly waves could be identified to have passed over this region and the time period of these waves are determined to be 4.2 days (4.5 days) by statistical methods (synoptic methods). The speed of movement, wavelength and amplitude of the waves are determined to be 7.28 ms-1, 2800 km and 6.7 ms-1 respectively. While rising motion is observed at most of the tropospheric levels over and behind the trough, subsidence occurs ahead of the trough. Divergence is noted over and behind the trough at upper troposphere while convergence occurs in the lower to mid-troposphere. Concomitantly warming is noted ahead of the trough while colder anomalies are noted in the lower levels over and behind the trough.